94 Essential oils improve barrier function and attenuate inflammatory responses in porcine intestinal epithelial cells. (5th December 2019) - Hui, Qianru; Omonijo, Faith; Liu, Shangxi; Zhang, Hua; Lahaye, Ludovic; Bodin, Jean-Christophe; Gong, Joshua; Nyachoti, Martin; Yang, Chengbo
Abstract: Thymol has been known as a functional phytochemical isolated from thyme essential oils and possesses antioxidant, antimicrobial, and anti-inflammatory properties. In this study, an in vitro lipopolysaccharide (LPS)-induced inflammation model using IPEC-J2 cell line was established to evaluate the inflammatory responses after thymol treatment. Cells were pre-treated with thymol for 1 h followed by LPS stimulation. Interleukin 8 (IL-8) secretion, reactive oxygen species (ROS) production, mRNA abundance of two pro-inflammatory cytokines, nutrient transporters, and tight junction proteins, transepithelial electrical resistance (TEER) and cell permeability were measured. The localization of zonula occludens-1 (ZO-1) and β-actin were also detected by immunofluorescent staining. The results showed that LPS stimulation increased IL-8 secretion, ROS production, and tumor necrosis factor alpha (TNF-α) mRNA abundance (P < 0.05), but the mRNA abundance of sodium-dependent glucose transporter 1 (SGLT1), excitatory amino acid transporter 1 (EAAC1) and H + /peptide cotransporter 1 (PepT1) were decreased (P < 0.05). However, thymol blocked ROS production (P < 0.05) and tended to decrease the production of LPS-induced IL-8 secretion (P = 0.0766). The mRNA abundance of IL-8 and TNF-α was reduced by thymol pre-treatment (P < 0.05), but thymol was unable to improve the gene expression of nutrient transporters (P > 0.05). TEER was reduced and cell permeability was increased after LPS stimulation (P < 0.05), but these effects were attenuated by thymol pre-treatment (P < 0.05). Moreover, thymol boosted ZO-1 and β-actin staining in the cells, but the mRNA abundance of ZO-1 and occludin-3 was not affected by either LPS or thymol treatments. These results indicated that thymol can enhance gut barrier structure and functions by reducing ROS production and pro-inflammatory cytokine gene expression in porcine epithelial cells during inflammation. The regulation of barrier function by thymol may be at post-transcriptional or post-translational levels.